Risk of thromboembolic events in women using combined oral contraceptives and hormone replacement therapy, and their prevention: a review - Nina A. Suricova; Anna S. Gluchova; Evgeny E. Kravchenko; Vladislav A. Vishnyakov; Evgeny I. Mokin (КардиоСоматика)
The risk of thromboembolic complications associated with the use of combined oral contraceptives (COCs) and hormone replacement therapy is a concern for both physicians and patients. The work aimed to analyze existing data on the use of COCs and their associated thromboembolic risk. This review summarizes the findings of Russian and international studies conducted in women using COCs who experienced thrombotic complications. A total of 37 sources were used, including articles indexed in international citation databases such as PubMed (MEDLINE) and Scopus, as well as foundational studies and monographs indexed in the Russian Science Citation Index (RSCI). Data were selected using the following keywords: сердечно-сосудистые заболевания (cardiovascular diseases), комбинированные оральные контрацептивы (combined oral contraceptives), КОК (COCs), тромбоэмболия лёгочной артерии (pulmonary embolism), ТЭЛА (PE), and инфаркт миокарда (myocardial infarction). Materials with unidentified authorship, educational manuals, pseudoscientific online sources, and publications not relevant to the topic were excluded.